2018
DOI: 10.18404/ijemst.440339
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Middle School Engineering Course on Students’ Academic Achievement and Non-Cognitive Skills

Abstract: 2018). The impact of a middle school engineering course on students' academic achievement and noncognitive skills. Abstract Article HistoryEngineering and integrated STEM experiences are being promoted at the K-12 level to increase interest and retention in STEM and to reinforce learning of mathematics and science content. However, research is still emerging regarding best practices for curriculum development, student impacts, and transfer of knowledge across disciplines. The purpose of this study is to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…A meta-analysis by Becker and Park [7] suggest that integrated STEM education has positive impacts on students' ability to transfer knowledge to new settings and problems. Consistent with this extant research, results of our recent study showed that the integrated engineering curriculum described in this paper significantly increased students' mathematics and science test scores [8]. In addition to investigating the transfer of specific knowledge within and across STEM disciplines, there is a long tradition of educational research concerned more generally with the extent to which the positive effects of a particular learning activity or intervention extend beyond the initial learning context [9].…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…A meta-analysis by Becker and Park [7] suggest that integrated STEM education has positive impacts on students' ability to transfer knowledge to new settings and problems. Consistent with this extant research, results of our recent study showed that the integrated engineering curriculum described in this paper significantly increased students' mathematics and science test scores [8]. In addition to investigating the transfer of specific knowledge within and across STEM disciplines, there is a long tradition of educational research concerned more generally with the extent to which the positive effects of a particular learning activity or intervention extend beyond the initial learning context [9].…”
Section: Introductionsupporting
confidence: 82%
“…Researchers have also investigated how integrated STEM curricula promote the transfer of knowledge from one STEM subject or context to another, ultimately enhancing student learning [6], [7], [8]. Because STEM integration supports the specific and explicit connection of topics from different disciplines, it may make the retrieval of knowledge more efficient when applying that knowledge in a new setting [6].…”
Section: Introductionmentioning
confidence: 99%
“…Common Problem-Based-Learning (PBL) activities in STEM classrooms today reflect the cognitive thought processes of engineers and are referred to as Engineering Design Challenges (Grubbs et al, 2018;Alemdar et al, 2018). Design challenge integrated learning experiences are now the preferred method of teaching STEM as these problem-solving practices are critical features of engineering education (Bartholomew et al, 2018).…”
Section: The "E" In Stemmentioning
confidence: 99%
“…These processes give K-12 students the opportunity to innovate and to operate within the realm of STEM in order to understand real world problem solving. Alemdar et al (2018) share their hypotheses that "applied engineering experiences that require active engagement with foundational mathematics and science…”
Section: The "E" In Stemmentioning
confidence: 99%
See 1 more Smart Citation